How to increase customer satisfaction of Mujair Fish Crackers with the IPA-KANO method - Muthiah, Imroatul; Ambarwati, Rita (MBR (Management and Business Review), 2023)
This study aims to analyze consumer satisfaction with the IPA-KANO method. This research uses quantitative research where data collection techniques using questionnaire. The respondents used in this study were 100 consumers of processed mujair fish cracker products CV. SARIRAM. The data analysis technique used in this research is the Importance Performance Analysis (IPA) method and Kano is then converted using SPSS. The results of the integration of Importance Performance Analysis (IPA) and the Kano model show that there are 12 attributes that fall into the category to be maintained and the remaining 8 attributes that need attention to improve their performance to increase customer satisfaction.